2021
DOI: 10.3390/w13010083
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Nitrate Sources in Rivers in a Complex Catchment Using a Dual Isotopic Approach

Abstract: Excessive nutrient input to surface water, including nitrate, exacerbates water eutrophication. Clarifying the proportions of different nitrate sources in the aquatic environment is critical for improving the polluted water. However, nitrate sources in river basins are very complex and not clearly understood. In this study, nitrogen concentrations and nitrate isotopic compositions were determined to estimate the spatiotemporal variation in nitrate sources in the Yuntaishan River basin, Nanjing, East China, fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Wastewater is a primary source of nitrate at low flows and baseflows across developed watersheds (Figures 3 and 5) (Divers et al., 2014; Guo et al., 2021; Kaushal et al., 2011; Potter et al., 2014; Xu et al., 2021). Our findings indicate that wastewater likely contributed 57% of nonpoint source baseflow nitrate loading.…”
Section: Discussionmentioning
confidence: 99%
“…Wastewater is a primary source of nitrate at low flows and baseflows across developed watersheds (Figures 3 and 5) (Divers et al., 2014; Guo et al., 2021; Kaushal et al., 2011; Potter et al., 2014; Xu et al., 2021). Our findings indicate that wastewater likely contributed 57% of nonpoint source baseflow nitrate loading.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [50] reported that nitrogen fertilizers, industrial discharge, municipal wastewater, animal waste, soil organic matter, and atmospheric nitrogen deposition are all potential causes of nitrate pollution in water. Numerous studies [18,20,51,52] have used stable isotope analysis, such as dual nitrogen and oxygen isotope ratios of nitrate, to identify nitrate pollution sources. Also, the sources of nitrate contamination in water have been found using relationships between nitrate, nitrite, ammonium, and chloride [42,53].…”
Section: Source Identification Of Nitratementioning
confidence: 99%
“…Nitrates present a complex challenge when establishing a threshold concentration due to their numerous natural and human-induced sources, as well as their reactivity [26,27]. Nitrate contamination is predominantly a concern in agricultural regions, with urban areas also affected to some extent [28,29].…”
Section: Introductionmentioning
confidence: 99%